Physiotherapeutic procedure on the example of compression therapy in treatment of venous diseases - Curyło, Mateusz; Cienkosz, Katarzyna; Mikos, Marcin; Czerw, Aleksandra Izabela; Raczkowski, Jan (Journal of Education, Health and Sport, 2018)
The aim of this study is an attempt to systematise the knowledge about physiotherapy in the process of treatment of vascular diseases, with particular focus on compression therapy. Moreover, an attempt was made to identify elements favouring the effective use of medical devices on the example of compression therapy.